Prototyping Vitruvius, new challenges: digital education, research and practice - Paio, A.; Eloy, S.; Rato, V.; Ricardo, R.; Oliveira, M.J. (Nexus Network Journal, 2012)
This paper discusses a key subject of research at ISCTE-IUL. Digital fabrication in architecture offers new perspectives and design innovation in three main areas: academia, research and professional practice. In order to investigate these new challenges and its contributions to architecture in Portugal, a group of multidisciplinary researchers organized a symposium that presented a state of the art in digital fabrication. The main points were the creation of the Vitruvius FabLab-IUL laboratory and the definition of appropriate new lines of research in digital fabrication.